1970
DOI: 10.1177/004051757004000409
|View full text |Cite
|
Sign up to set email alerts
|

A New Catalyst System for Cross-Linking Cotton Cellulose with Formaldehyde

Abstract: A dual catalyst system containing magnesium and fluoborate ions facilitates the cross-linking of cotton cellulose with formaldehyde. Compared with previous formaldehyde cross-linking processes, the dual catalyst system permits operating at lower temperatures, shorter curing times, and lower concentrations of formaldehyde to produce high and nonvariable wash-wear characteristics which are durable in home and commercial launderings. In addition, this dual catalyst system may be used to impart durable-press prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1973
1973
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Both Zn(BF4)2 and NaBF4 have calculated constants close to that reported for HF; the constant for Mg(BF4)2 is two orders of magnitude greater. Kravetz and Ferrante reported contributions of hydrolysis of NaBF4 to the acidity of the NaBF4: MgCl2 mixed catalyst system used in a 1:10 gfw ratio in crosslinking treatments with formaldehyde [8]. They state that the BF3 produced from hydrolysis reacts synergistically with MgCl2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Zn(BF4)2 and NaBF4 have calculated constants close to that reported for HF; the constant for Mg(BF4)2 is two orders of magnitude greater. Kravetz and Ferrante reported contributions of hydrolysis of NaBF4 to the acidity of the NaBF4: MgCl2 mixed catalyst system used in a 1:10 gfw ratio in crosslinking treatments with formaldehyde [8]. They state that the BF3 produced from hydrolysis reacts synergistically with MgCl2.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium fluoborate, although not a highly efficient catalyst by itself [8,13], has been discussed previously for inclusion in mixed catalyst systems with magnesium chloride in DP finishing [4,8,9,13]. Both the classical treatment of sodium fluoborate [11,15] and recent textile literature [8,9,13] consider sodium fluoborate, the salt of a hard acid and a hard base, to be a neutral salt. The textile literature claims that it is activated in the presence of MgCl2 by Lewis acid activity [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increased catalytic activity of a mixed catalyst system had been attributed to increased protonation during the reaction and consequent liberation of a strong volatile acid [7,12]. This concept was not acceptable to others on the grounds that, if the liberation of a strong volatile acid had been the main cause for increased effectiveness of a mixed catalyst system, there should be more loss in strength, which is contrary to the observation that the relationship between WRA and strength retention improves when a mixed catalyst system is used in place of a single catalyst [5,6,10,13,16]. Pierce and Frick made a detailed study of a mixed catalyst system (magnesium chloride hexahydrate and citric acid) and found that the mixtures exhibited more catalytic activity than either component used separately.…”
Section: Mechanism Of Catalysismentioning
confidence: 99%